Artificial intelligence (AI) in nursing administration: Challenges and opportunities - Omar Qaladi; Mukhlid Alshammari; Abdullah Abdulrahim Almalki (PLoS ONE, 2025)
Artificial Intelligence (AI) is increasingly transforming nursing administration by enhancing operational efficiency and supporting data-driven decision-making. This study explores registered nurses perceptions of AI in Saudi Arabia, focusing on both challenges and opportunities. A cross-sectional survey of 202 nurses revealed that 93.6% believe AI improves understanding, and 88.1% feel it enhances the quality of learning. Significant correlations were found between years of experience and AI usage (r =  0.342, p <  0.001) and between sources of information and AI perception (r =  0.146, p =  0.039). While 80.7% expressed concern that AI could reduce critical thinking, 76.8% feared job displacement. These findings underscore the need for training, ethical guidelines, and support systems to foster effective AI integration, enhancing nursing practice while addressing concerns around professional roles.